To solve the equation \( 5(25 + 15x) = 3x + 5 \), let's first expand and simplify both sides.
-
Distribute \( 5 \) on the left side: \[ 5(25 + 15x) = 125 + 75x. \]
-
Rewrite the equation: \[ 125 + 75x = 3x + 5. \]
-
Now, let's get all terms involving \( x \) on one side and constant terms on the other side. Subtract \( 3x \) and \( 125 \) from both sides: \[ 75x - 3x = 5 - 125. \]
-
Simplify: \[ 72x = -120. \]
-
Now, solve for \( x \): \[ x = \frac{-120}{72}. \]
-
Simplify the fraction: \[ x = \frac{-5}{3}. \]
Since the equation \( 5(25 + 15x) = 3x + 5 \) resulted in a single value for \( x \), we conclude that there is one solution to the equation.
Enter your answer on Zearn as One solution.